2012
DOI: 10.3402/jom.v4i0.10123
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas endodontalisin chronic periodontitis: a clinical and microbiological cross-sectional study

Abstract: BackgroundAlthough previous studies have shown the presence of Porphyromonas endodontalis in chronic periodontitis associated with periapical lesions, the occurrence of this pathogen in diseased periodontal sites without periapical lesions has been poorly investigated.ObjectiveThe aims of this study were to quantify P. endodontalis in patients with chronic periodontitis without periapical lesions, to evaluate the potential correlation of P. endodontalis with Porphyromonas gingivalis and Tannerella forsythia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…The average number of taxa at the species level per individual (16) that we found was lower than what has been reported in other studies, which is around 200-600 species (13, 30). This is probably because the 16s RNA fragment we have used had a relatively low capacity to discriminate within the lowest taxonomic levels (genus and species).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The average number of taxa at the species level per individual (16) that we found was lower than what has been reported in other studies, which is around 200-600 species (13, 30). This is probably because the 16s RNA fragment we have used had a relatively low capacity to discriminate within the lowest taxonomic levels (genus and species).…”
Section: Discussioncontrasting
confidence: 95%
“…Due to the relationship between Diabetes and periodontal disease, we compared the relative abundance of species that have been related to periodontal disease ( Prevotella intermedia, Campylobacter rectus, Porphyromonas endodontalis , and Treponema socranskii and TG5 spp . (16-19)), and they were almost vestigial in both groups. TG5 spp.…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, 1 Cold OTU was identified as Actinomyces oris , which was not highly abundant in periodontitis patients53. Only 2 Cold OTUs identified as Porphyromonas endodontalis have been reported as possibly pathogenic in periodontitis52. Therefore, tongue-microbiome analysis provides new findings that effectively explain Hot Syndrome in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have reported the presence of additional subgingival bacterial species in diseased periodontal sites 1,2 . Among these pathogens, Porphyromonas endodontalis, an asaccharolytic, black-pigmented, Gram-negative anaerobic bacteria, is noteworthy 3 .…”
Section: Introductionmentioning
confidence: 99%